MANAGEMENT MODEL OF TEACHER’S JOB DESCRIPTION FOR PRODUCTIVE PROGRAM PRACTICE OF STATE VOCATIONAL SCHOOLS - Hadromi, Hadromi (The Journal of Educational Development, 2013)
Teacher’s job description on the productive program practice consist of such activitiesas planning, implementation, evaluation of productive program practice output,giving guidance and training to students, and doing additional tasks other than theirmain task. The teachers implement their job description in teaching and learningprocess by teaching one subject in accordance with their the certified qualification.In addition, the teachers are involved in school management activities includingnew students enrolment, curirculum preparation and its supporting documents, nationalexamination, school examiantion and others. The teacher’s job description isspecifically determined by the school management and their teaching load consistsof 24-40 credit units, based on the their skills, usefulness and equal distribution